The Impact of Manufacturing Industries on Economic Growth in the Kingdom of Saudi Arabia during (1990- 2018) - Al-Ghamdi, Reem Saeed; Alandejani, Maha (Journal of Economic, Administrative and Legal Sciences, 2020)
The study examined the effect of the impact of manufacturing industries on the economic growth in the Kingdom of Saudi Arabia، and to analyze the size of manufacturing growth and its contribution to economic growth. This study is based on the descriptive analytical approach to identify the development of manufacturing industries in Saudi Arabia and the size of its impact on the growth of the Saudi economy and also based on the methodology of standard analysis using time series data، and the application of unit root testing and common integration and multiple linear regression by applying an Ordinary Least Square (OLS)، to examine the relationship between the rate of economic growth، the rate of GDP of manufacturing، the rate of oil exports، the rate of industrial loans، and the rate of exports of manufacturing industries. The results indicate to negative impact of manufacturing industries، oil exports and industrial exports on economic growth in the long term، despite their positive impact in the short term and the existence of a direct correlation between the rate of growth of oil exports and economic growth in the short term، and the inverse relationship of industrial loans and industrial exports on economic growth. The study summarized several recommendations، including that decision-makers need to pay attention to manufacturing industries and oil exports taking into account the long- term risks of global oil markets and import prices، and the adoption of more extensive policies with regard to industrial loans and maximize industrial exports to affect economic growth positively.
Keywords: Manufacturing industries; Economic growth